INVESTIGATION OF ANTIMICROBIAL, ANTIOXIDANT AND ANTICANCER EFFECTS OF TRADITIONAL SPICES MIX - Dalkilic, Lutfiye Kadioglu; Inci, Sule; Dalkilic, Semih; Kirbag, Sevda (Parlar Scientific Publications (P S P), 2020)
Thanks to their spices, flavors and aromas, they are one of the most important foods to be consumed for health as well as adding flavor to food. They are used for human health by drying the different plant extracts, sometimes mixing them and sometimes using them alone. These spice mixtures are known to have medicinal effects such as antioxidant, antimicrobial, anticancer, anti-inflammatory, antihelminthic, immunomodulator. Em, which is used in this study, was obtained by mixing various spices in Gaziantep region. It is known to be good for women after childbirth. In this study; it was aimed to determine the antimicrobial activity of different concentrations of extracts of Em obtained using solvents such as methanol, ethanol and hexane, the antioxidant activity of different concentrations of extract obtained using methanol and the anticancer activity of different concentrations of extracts obtained using methanol and ethanol, Antimicrobial activity was determined by disc diffusion method. Bacteria such as Staphylococcus aureus ATCC25923, Klehsiella pneumoniae ATCC700603, Escherichia coli ATCC25322 and Bacillus megaterium DSM32 and Candida albicans FMC17 were used as fungi. Antioxidant activity was determined according to 2,2-dipheny1-1-picrilhydrazil (DPPH) method. The anticancer activity was determined according to the MTT (3- (4,5-dimethylthiazol-2-yl) -2,5-diphenyltetrazolium bromide) assay method. Em's ethanol extract showed the best antimicrobial activity against K. pneumoniae (18 mm) at a concentration of 200 mg / ml. DPPH radical scavenging effect was found to increase with increasing concentration. According to MTT assay results, MDA-MB-231 (breast cancer) and PC3 (prostate cancer) showed significant cytotoxic activity against cell lines.
Keywords: Antimicrobial activity; Antioxidant activity; Anti-cancer; Spices